Development of innovative systems and indicators fpr sustainable shellfish farming - De Marco, Antonina <1994> (Alma Mater Studiorum - Università di Bologna, 2024)
Shellfish farming plays an important role in world aquaculture, with total production being over 25%. It is threatened by climate change. In particular, predictive models show there will be more frequent, intense and lasting heat waves. In this thesis, three shellfish species, the Pacific oyster Magallana gigas, the striped venus clam Chamelea gallina and the Mediterranean mussel Mytilus galloprovincialis, were exposed to a heat wave of 28°C± 0.5°C for 30 days, as predicted for the northern Adriatic in the coming years. Biometric, physiological and hemolymphatic parameters were assessed during the prolonged thermal stress, including heat shock proteins (HSP) 70, 72, 90 and factor p53 gene expression for M. gigas; ability to survive at aerial exposure and the synthesis of HSP70 for C. gallina; performances of the byssus for M. galloprovincialis. During 10 days of high temperature, the M. gigas metabolism is affected by loss in weight, in energy resources, reduction of nutrient absorption and pulp yield, an over-expression of HSPs. This thermal effect could lead to reduced productivity and salable products. C. gallina, remains slightly affected, using the energy resources of hepatopancreas but increasing the ability to survive at air and inhibiting the synthesis of HSP70. Their remarkable thermal resistance highlights their suitability for shellfish aquaculture. M. galloprovincialis showed an intermediate response compared to the two molluscs mentioned above: no reduction in pulp yield but in the energy resources, air survival, number and strength of byssus with altered structure. These changes could increase the risk of loss of the farmed product, by breaking the byssus that keeps the mussels tied to the nets. With these studies an attempt has been made to provide tools to understand what to expect about the trend of the shellfish aquaculture in the future in a changing and warming climate.